Influence of surfactant type on the microstructure, mechanical and thermal properties of phenolic foams - Mohammad Hamid Shadnia; Sajad Rasouli; Mohammad Fasihi (Scientific Reports)
Abstract Surfactant chemistry can affect the phenolic foam (PF) properties by controlling the collision and combination of the created bubbles during foam production. The study was accomplished using two surfactant families, nonionic: polysorbate (Tween80) and anionic: sodium and ammonium lauryl sulfates (SLS30 and ALS70) and sodium laureth sulfate (SLES270) to manufacture PF foams. Tween80 and SLS30 resulted in foams with the lowest and highest densities, 20.2 ± 0.2 and 42.72 ± 0.4 kg/m3, respectively. All the surfactants created an open-cell morphology, except Tween80 with a semi-open-cell structure consisting of large cells and thicker cell wall thickness. The anionic surfactant had better performance, the foams made by SLS30 had cells with diameters of 338.5 ± 18.5 and cell density of 2.5 cell/mm3 × 105. While the SLES270 made foam with the highest cell density and the smallest cell size that caused higher compressive strength. The SLES270 led to keeping the foam flexibility even under the fire exposition, and it increased the thermal insulation by 50% while the other samples were turned into fragile foam. A higher level of polarity in SLES270 caused better micelle production and then better bubble formation, followed by the bubble coalition.